2000
DOI: 10.1073/pnas.97.16.9287
|View full text |Cite
|
Sign up to set email alerts
|

Spinophilin regulates the formation and function of dendritic spines

Abstract: Spinophilin, a protein that interacts with actin and protein phosphatase-1, is highly enriched in dendritic spines. Here, through the use of spinophilin knockout mice, we provide evidence that spinophilin modulates both glutamatergic synaptic transmission and dendritic morphology. The ability of protein phosphatase-1 to regulate the activity of ␣-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) and N-methyl-D-aspartate (NMDA) receptors was reduced in spinophilin knockout mice. Consistent with altered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
341
2
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 359 publications
(353 citation statements)
references
References 51 publications
9
341
2
1
Order By: Relevance
“…This is exemplified by experiments showing that loss of tPA or plasminogen conferred neuronal protection after excitotoxic injury (Tsirka et al, 1995) and stroke (Wang et al, 1998). Several other proteins have been identified whose absence confers resistance to excitotoxin-induced neuronal degeneration: jnk3 (Yang et al, 1997), preprotachykinin A (Liu et al, 1999), glutathione peroxidase (Jiang et al, 2000), and spinophilin (Feng et al, 2000). It is not clear that all of these players lie in the same pathway for neurodegeneration, but loss of any of these components provides some degree of neuroprotection.…”
Section: Discussionmentioning
confidence: 99%
“…This is exemplified by experiments showing that loss of tPA or plasminogen conferred neuronal protection after excitotoxic injury (Tsirka et al, 1995) and stroke (Wang et al, 1998). Several other proteins have been identified whose absence confers resistance to excitotoxin-induced neuronal degeneration: jnk3 (Yang et al, 1997), preprotachykinin A (Liu et al, 1999), glutathione peroxidase (Jiang et al, 2000), and spinophilin (Feng et al, 2000). It is not clear that all of these players lie in the same pathway for neurodegeneration, but loss of any of these components provides some degree of neuroprotection.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced mRNA expression of cell division cycle 42, which promotes dendritic spine outgrowth (Irie and Yamaguchi, 2002), and Kalirin 7, which is necessary for both spine outgrowth and mediates LTP-induced spine structural plasticity (Penzes et al, 2001), was found in PFC, and correlated with reductions in spine density (Hill et al, 2006). Of interest, spinophilin has been recently shown to be a mediator of LTD-, but not LTPinduced structural plasticity (Feng et al, 2000). These effects are mediated via recruitment of the Rho guanine exchange factor, Lfc (Lbc (lymphoid blast crisis)'s first cousin), into spines (Ryan et al, 2005), and via targeting of protein phosphatase 1 to glutamate receptors within spines (Feng et al, 2000) and to actin (Fernandez et al, 1990).…”
Section: Implications For Auditory Cortical Development In Schizophreniamentioning
confidence: 99%
“…Of interest, spinophilin has been recently shown to be a mediator of LTD-, but not LTPinduced structural plasticity (Feng et al, 2000). These effects are mediated via recruitment of the Rho guanine exchange factor, Lfc (Lbc (lymphoid blast crisis)'s first cousin), into spines (Ryan et al, 2005), and via targeting of protein phosphatase 1 to glutamate receptors within spines (Feng et al, 2000) and to actin (Fernandez et al, 1990). As reviewed above, there is evidence to suggest spinophilin expression is increased or unchanged in cortical extracts of subjects with schizophrenia.…”
Section: Implications For Auditory Cortical Development In Schizophreniamentioning
confidence: 99%
See 1 more Smart Citation
“…Neurabin (1) and spinophilin (2)(3)(4) are neuronal scaffolding proteins that play important roles in synaptic transmission and synaptic plasticity (5,6). Neurabin and spinophilin are highly enriched in dendritic spines, the site of excitatory neurotransmission.…”
mentioning
confidence: 99%